Advanced Oxidation Protein Products and Carbonylated Proteins Levels in Endovascular and Open Repair of an Abdominal Aortic Aneurysm: The Effect of Pre-, Intra-, and Postoperative Treatment. (8th May 2019) - Gryszczyńska, Bogna; Budzyń, Magdalena; Formanowicz, Dorota; Formanowicz, Piotr; Krasiński, Zbigniew; Majewska, Natalia; Iskra, Maria; Kasprzak, Magdalena P.
Abstract : Background . In recent years, a rapid increase in studies focusing on the role of oxidative stress in the pathogenesis of an abdominal aortic aneurysm (AAA) has been observed. Oxidative modifications of proteins are infrequently evaluated in reference to AAA. Objectives . The intensity of oxidative protein modifications, presented as advanced oxidation protein products (AOPP) and carbonylated proteins (C=O), in AAA patients qualified for surgery was estimated. The effect of surgical techniques and intraoperative and postoperative treatment on AOPP and C=O levels was evaluated. Patients . The EVAR group, consisting of 30 patients, was classified for endovascular aneurysm repair, whereas 28 patients were classified for conventional open repair (OR). Methods . AOPP and C=O were measured using a colorimetric assay kit. Results . A significantly lower AOPP level obtained 2-4 days after EVAR surgery in comparison with the value found before surgery was noted. In the case of OR postoperative treatment, a tendency of AOPP level to increase was observed. The tendency of C=O to decrease after surgery in the EVAR group was indicated. However, the C=O level tended to increase after OR surgery and reached a significantly higher value 5-7 days after surgery compared with the value obtained before surgery. Conclusions . Based on our results, it may be concluded that AAA as well as surgical technique contribute to the formation of AOPP and C=O. The analysis of changes in AOPP and C=O values obtained after surgery revealed a significant effect of a patient's condition before surgery as well as the choice of surgery technique on the values of the studied parameters revealed during postoperative treatment.